China in Sri Lanka - DIAS, Galagama Sachini (KDI School, 2022)
The ‘Belt & Road Initiative (BRI)’ is the 21st century grand strategy of China which envisages the construction of massive industrial corridors and connectivity networks across land and sea. Expanding from China to Europe via South East, South and Central Asia, this policy initiative has brought forth significant transformations to the political, economic and strategic aspects of the global power order, re-emerging China as a revisionist power and re-surging the centuries old Asian order. In response, there has been a growing interest in the existing literature to analyze the context of BRI through diverse concepts and frameworks. The debt trap which implies the ‘debt to equity’ transfers is one such debatable concept which has been used by the growing body of literature to interpret the context of the BRI. The Indian Ocean island nation, Sri Lanka has been widely narrated in the literature and policy circles as a victim of Chinese debt trap. In this backdrop, the purpose of this research paper is to quantitatively and qualitatively analyze Sri Lanka’s BRI project profile, investments and debt profile in order to identify as to whether the BRI in Sri Lanka resembles a debt trap. This paper also attempts to identify the implications and possible tendencies of the BRI in Sri Lanka, re-examining the question of why do the policy makers in the developing world need to rethink China''s approach. Traversing on the interpretative and evaluative case study method of qualitative research paradigm, this research paper concludes that BRI in Sri Lanka is a greater economic and development opportunity which has supported the country to fulfill its infrastructure gap in diverse sectors in Sri Lanka. Although the study identifies that several BRI projects as economically non-viable initiatives, based on the statistical evidences, this paper concludes that the debt crisis of the country as a long preceding structural issue of the economy made by Colombo, not an intended trap of China, counter arguing that the China in Sri Lanka as not a debt trap.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Yi dai yi lu (Initiative : China)